(untitled) (CAHIERS MAGELLANES-NS, 2024)
The article presents the results of research conducted on the study of the processes that occurred in the water-physical parameters of the stands during the maintenance of cotton varieties under different irrigation technologies in the conditions of automorphic gray soils of the Tashkent region. In this, 3 (S-6524 and new S-6570 and S-8298) varieties of cotton were studied under irrigation and drip irrigation (TS). In the experiment, irrigations were carried out in different order (65-70-65 in TS, and 70-70-60 percent in control watered with 70-75-65) depending on the limited field moisture capacity (field wet capacity) of the soil. As a result of scientific research, in drip irrigation medium fiber cotton varieties S-6524, S-6570 and S-8298 compared to field wet capacity at 70-70-60% and 70-75-65% pre-irrigation soil moisture when irrigated 12-13-14 times S- 6.2-5.1-8.8 cotton yield was obtained in 6524 cotton variety, 42.5 s/ha in S-6570 cotton variety, and 46.2 s/ha in S-8298 cotton variety, compared to 6.2-5.1-8.8 s/ additional harvest was achieved.